The Organization of Biosphere Compatibility Construction : Justification of the Predictors of Building Development and the Implementation Prospects - Chernyshev, Denys; Ivakhnenko, Iryna; Klymchuk, Maryna (International Journal of Engineering and Technology, 2018)
The article considers the modern practice of urban innovation, based on the principles of biosphere compatibility. The project solution of providing organizational and technological reliability of construction from the point of view of the possibility of realizing the functions of a biosphere compatibility city and introducing innovative constructive and architectural and planning solutions is analyzed. In relation to the construction project, the formalization of the methodology for calculating the indicators of the biosphere compatibility of cities and settlements, the quantitative indicators of the implementation of the functions of the city are determined. The obtained results of numerical analysis of the realization of city functions can predict the development of urban areal, assess the comfort and safety of the urban environment from the standpoint of biosphere compatibility of construction objects in order to harmonize the characteristics of the life cycle of these projects with the characteristics of the microenvironment of their implementation. The basis of such tools is: multifactorial, multicomponent modeling and multicriterial selection of alternatives for building construction for projects, provided that the level of biosphere compatibility is used as the leading analytical coordinate of such simulation. These models, implemented in the format of modern construction, will serve as a basis for organizational and technological and environmental expertise of projects.Â Â